Juri Lomba Olimpiade Ekonomi Islam Temilreg Fossei Sumbangsel 2020 Dengan Tema “Optimalisasi Ekonomi Digital Untuk Mendukung Halal Life Style Guna Menjadikan Indonesia Sebagai Pusat Ekonomi Syariah Dunia.” - Choirunnisak Choirunnisak (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2020)
Indonesia is preparing to face the challenges and opportunities for the development of the halal industry. Where Indonesia is expected to become the center of the World Halal Industry. Currently Indonesia is able to fill the world's halal industry. This will certainly be a good potential for the future.